PISCICULTURA; INDÚSTRIA DE VIDROS PLANOS; COMÉRCIO; LOGÍSTICA DE ARMAZENAGEM: v. 1 n. 3 (2016) - Vidal, Maria de Fatima; Freire, Laura Lúcia Ramos; Damasceno, Wellington Santos; Viana, Fernando Luiz E. (Caderno Setorial ETENE, 2024)
.